Persistence and engagement among first-year Hispanic students. Issue 2 (10th June 2019) - Luciano-Wong, Shaila; Crowe, Dale
Abstract : Purpose: The purpose of this paper is to examine the association between engagement indicators and intent to persist of first-year full-time Hispanic students attending public versus private universities. Design/methodology/approach: Metadata from the Your First College Year survey from the Higher Education Research Institute (HERI) were selected for this study. The approach included using a descriptive correlational design and regression analysis to examine the relationship between engagement indicators and persistence among first-year, full-time Hispanic students and persistence. Purposeful sampling obtained from the HERI data set resulted in a sample size of 1, 206 students who attended public institutions and 1, 187 students who attended private institutions. Findings: Analysis of the results disclosed a positive correlation between first-year Hispanic students' intent to persist, satisfaction with peer interactions, amount of contact with faculty, first-year programs and sense of belonging. The results of the analysis disclosed differences between public and private institutions. Of the collective variables, satisfaction with amount of contact with faculty and sense of belonging are significant predictors of persistence. Research limitations/implications: The sample of the study was limited to the use of archival data and the responses to specific questions obtained from the 2014 YFCY survey. Factors such as insufficient experience at the college students are attending, unwillingness to provide honest feedback and exaggerating specific areas of their behavior or performance may affect students who respond to surveys (Kuh, 2004), affecting the accuracy of the data. Further, 89.7 per cent of the variance in persistence has not been explained. Adding or using different variables and utilizing a more advanced statistical technique may account for additional variance. Cause and effect cannot be determined from correlational analysis, and the possibility exists that an unknown variable may be the cause of a correlation within the study. Incomplete information from predictors, complete separation and overdispersion can lead to SPSS output errors for logistic regression analysis. Social implications: It is important for higher education administrators to understand the cultural differences of not only Hispanic students but other ethnic and racial groups. As a global society, public and private higher education institutions are looking for more inclusion of multi-cultural students. Recruitment is obviously important, but to recruit is not enough. It is the responsibility of higher education administrators to do all that is reasonably possible to retain students through graduation. Originality/value: Studies have been conducted on academic disparities between Hispanic students and their White counterparts, but few studies exist on the factors associated to persistence among the first-year Hispanic student population. The results of this study may add to the existing body of knowledge and assist with faculty development of programs, decisions on class size, improvements to pedagogy and discussions to improve the campus climate for Hispanic students. Using the resources of HERI, future studies can be conducted involving other races and ethnicities.